Anodal transcranial direct current stimulation over the auditory cortex improved hearing impairment in a patient with brainstem encephalitis. (June 2016) - Mori, Takayuki; Takeuchi, Naoyuki; Suzuki, Sakiko; Miki, Mika; Kawase, Tetsuaki; Izumi, Shin-Ichi
Transcranial direct current stimulation (tDCS) can alter cortical excitability, and has been effective in treating some neurological disorders. This case report describes the use of tDCS in a 13-year-old female who developed bilateral hearing impairment after brainstem encephalitis when she was 6 years old. Her auditory function was more impaired in her right ear than her left. Anodal stimulation (1 mA) was applied for 10 min to the left auditory cortex once per day for 4 consecutive days to improve her right ear speech discrimination score. Sustained and significant improvement in maximum speech discrimination was observed after the four tDCS treatments. To our knowledge, this is the first case report of improvement in speech discrimination after anodal stimulation of the auditory cortex. These results encourage further studies investigating the beneficial effects of tDCS in patients with hearing impairments.